Burden of Aeromonas hydrophila –associated diarrhea among children younger than 2 years in rural Egyptian community - Mansour, Adel M; Abd Elkhalek, Rania; Shaheen, Hind I; El Mohammady, Hanan; Refaey, Samir; Hassan, Khaled; Riddle, Mark; Sanders, John W; Sebeny, Peter J; Young, Sylvia Y.N.; Frenck, Robert (Journal of infection in developing countries, 2012)
Introduction: Between 2004 and 2007, a birth cohort of Egyptian children was analysed to evaluate the epidemiology of enteric diseases. Methodology: A stool sample was collected from the study children every two weeks as well as whenever they experienced diarrhea. Samples were tested for routine bacterial pathogens as well as enteropathogenic viruses and parasites. A secondary goal of the study was to evaluate the burden of less commonly reported pathogens including Aeromonas hydrophila. Results: Of the 348 study subjects, 79 had A. hydrophila isolated from their stool at some point during the study.  Thirty-six children had exclusively symptomatic (S) infections while 33 had exclusively asymptomatic (AS) infections. However, 10 children had both S and AS infections. Among symptomatic cases, A. hydrophila was the sole pathogen isolated 36% of the time. An important aspect of A. hydrophila associated diarrhea was the high level of resistance to cephalosporins. Conclusion: Although relatively uncommon, A. hydrophila was found to be associated with diarrhea among children living in Egypt and was frequently multi-drug resistant.